INVESTIGATION OF PARAMETERS AFFECTING LOST FOAM CASTING (Journal of Engineering, 2009)
The lost-foam casting process using expanded polystyrene foam pattern allows more complex and detailed passages to be cast directly into the part. The advantages of the lost-foam casting process involve, forms complex internal and external shapes without cores, reduces part mass with near net-shape capability, eliminates parting lines, and reduces machining operation and costs, Complex shapes with various sizes castings were produced in this technique in the foundry of the State Company for Electrical Industrials to evaluate the process. Successful complete castings were made. Many experimental works were done to further complements about fluidity parameter dealing with lost-foam casting process. Empirical linear and non-linear formulas were obtained from those experimental works to find the minimum temperature for pouring molten metal. Aluminum alloys were the material of choice for this work, due to the best combination of mechanical properties and castability, but the performance requirements and manufacturability issues will drive the choice of a specific aluminum that was aluminum-silicon alloy, which were used in this work.The macroscopic properties of the alloy depend strongly on the microstructure. Therefore, photomicrographs of microstructures of various castings with different foam pattern densities were done and made comparisons with common sand castings. Mechanical tests were conducted on the castings which produced by the common sand casting and the lost-foam casting processes. These tests include tensile, hardness, and impact. Because of using the expandable polystyrene as a pattern that gave, more gasses in the cavity of the mold during casting, so the mechanical tests show some differences between the two processes.